Understanding concussion knowledge and behavior among mixed martial arts, boxing, kickboxing, and muay thai athletes and coaches - Follmer, B.; Varga, A. A.; Zehr, E. P. (The Physician and Sportsmedicine, 2020)
Objectives: In combat sports, strikes to the head are not just incidental but a deliberate and clear determinant of success. Concussion is a complex injury that is poorly understood and inappropriate practices are often observed among athletes and coaches. The purpose of this study was to investigate concussion knowledge and behavior as well as address recommendations for combat sports athletes and coaches.